Public Theology as Cultural Witness: Christological Contours for “Times That Are A’Changin’” - Christine Schliesser (Religions, 2023)
Churches in Europe are being faced with a transformation that can be described as a seismic shift. In order to face the challenge of cultural witness in this context, this contribution proposes a Christologically contoured public theology. This will be spelt out in four consecutive steps. After a brief introduction on the paradigm of public theology, the second part tackles the question of addressees. Is the witness of public theology directed at the church or at the world? Making use of the insights of German theologian Dietrich Bonhoeffer, this contribution argues for going beyond the binary and understanding the one Christ-reality as the frame of reference for public theology and cultural witness. The third part seeks to uncover the transformative power of Christology for public witness by making use of the traditional dogmatic figure of the munus triplex for the task of witnessing to the “public Christ” (Michael Welker). In the final part, three theses sketch out the implications of public witness in “times that are a-changin’.” (1) Public witness needs religious literacy and bilinguality. (2) For public witness, diaspora existence and missional existence are sisters. (3) Public witness is ecumenical, practical, and spiritual.